Combining ability of S3 maize inbred lines and related contributing traits for high yield under high population density. Issue 1 (November 2021) - Efendi, Roy; Slamet Bambang, P.; Arif Subechan, M; Aqil, M.; Azrai, M.
Abstract: The productivity of maize may be increased by using maize hybrid ideotype (erect leaves and small leaf angles) which is adaptive under high plant population density. The hybrids maize was desirable in increasing the plant density due to better light interception and space so that it can increase the yield per unit area. The aim of the research was to assess S3 lines that had good combining ability and to determine the traits associated with high yields under high plant population density (83.333 plants/ha). A total of 242 hybrids (F1) were examined from a crossed combination of 121 lines x 2 tester were evaluated with three commercial hybrid varieties such as Bisi 18, P 27, and P 36. The evaluation was carried under high plant population density (83, 333 plants/ha) in the rainy season (November 2020 – February 2021). The research used an alpha lattice design with three replications. The results showed that the inbred lines had a greater effect on the yield character and yield components, while the leaf angle and leaf orientation effected by the tester. The lines that had good general combining ability for high yielding were M3B11P27T3-11-3-1, P27M3B11T3-1-4-2, P27M3B11T3-1-2-1, M3B11P27T3-8-4-1, P27M3B11T1-7-1-1, M3B11P27T1-1-1-3. The yield range of the hybrids were 8.43-9.90 t/ha, significantly higher than Bisi 18, P 27, P 36 varieties were 7.13 t/ha. Traits such as small leaf angle, erect leaf, root and stem lodging resistance, stem diameter, leaf length, ear diameter, and kernel row number were significantly correlated with high yield under high plant population density.